A gyermekáldás mint örömforrás, – vagy szenvedés?2 - PÜSÖK, Sarolta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2015)
The childbirth as a source of joy or misery. Th s study is a short presentation of ambivalent approach to the childbirth, and shows us the current disappointing situation, and is trying to point out the solution. The short history of this issue presents that in ancient East the child was like an asset (for example in Hamurapi Code or Torah), gift of gods. In Old Testament in contrast with the surrounding religions, the people asked God for children not by cultical prostitution but by payer. Th child as source of suffer highlights that in history of humanity we find the child’s rejection everywhere: in texts of Plato, Aristotle and Hippocrates Oats, the cruel practice in Sparta, the strict abortion laws in 20th century or the contradictory situation: the Chinese birth control –these are the many aspect of this question. Th Hungarian pastoral psychologist, Gyökössy Endre gives a very important ad- vice: in christian marriage the childbirth is not only the woman’s affair. Abortion survivor – is a relative new psychological concept, it affects far more peo- ple than we’d think at first hearing. Anyone can be considered an abortion survivor, whose parents would have aborted them if they had the chance like the Romanian “decreței” (Children born because the abortion ban). This category of people often suffer from a lack of confidence. An only child – it is the tragic keyword of contemporary European society. How many children have to be born in a family? The answer is not obvious, it can not be generally prescribed, it depends on the individual situation too. But it is clear, the child-bearing habits can be only changed when first there will be a change in the way of thinking ,in the relationship with God. The solution is the turning to God.